"Thinking out loud" about cognition in orienteering - Johansen, B. (Sportscience)
Doctoral candidate Bjorn Tore Johansen discusseshis "think out loud" technique for studying cognition in orienteering, and speculates on ways the method may be useful in training for other sports as well.